(Re) construção de conhecimentos dos alunos da educação de jovens e adultos por meio do educar pela pesquisa - Brandolt, Thelma Duarte Delgado (2013)
With the purpose of investigating which contributions for the educating through research for the (re) construction of the knowledge of the students of youth and adults education, this research was developed on the form of a case study with students from a class in the stage VIII at a state public school in the west border of Rio Grande do Sul state. The suggested teaching situations were planned considering the research as an educational principle and its moments of questioning, construction of arguments and communication. For that, as a triggering factor, the work started from a problem situation based on real facts called The Mistery of Carvalho Family . For that, it was used as instruments of the data collection: questionnaires - initial and final -, audio recordings, the researcher's field journal, besides the student‟s productions during the sequence of the developed classes, such as, for example, posters, games, conceptual maps and texts made by the class. The achieved information were submitted to Discursive Textual Analysis (MORAES; GALIAZZI, 2011). From this qualitative analysis, three categories came out. On the first of them: The awakening of the attitude contents it is discussed the necessity of attention to the affective dimension of the teaching and learning processes, in special, on youth and adults education. The second category is called The complexification of the conceptual contents and it is analyzed on it the evolution of the concepts during the sequence of the planned classes. The qualification of the procedural contents represents the third and last category in which the considered abilities are approached during the classes. At the end of this investigation, it was understood that the work performed was in accord with the Educating through Research at EJA is a possibility on the qualification of the teaching practice on this distinguished segment and attention to the characteristics of the students. In addition to this, when embracing different kinds of contents (attitudinal, conceptual and procedural), the practice of Educating through Research indicates ability to help for the (re) construction of the knowledge of youth and adults education, dealing, therefore, of a way of considering the student as a whole. During the investigation, it was pointed out the concern of the people involved with the occurrence of visceral leishmaniasis and its consequences in the city and its surroundings.